Exploring Acculturation Experiences and Cultural Dialogues among Iranian Refugees in the Netherlands by Means of the Self-Confrontation Method - te Lindert, Annet; Korzilius, Hubert (Studia Psychologica: Theoria et praxis, 2008)
In this study we explored the most important topics of acculturation experiences among Iranian refugees in the Netherlands, using the Self-Confrontation Method (Hermans & Hermans-Jansen, 1995). We discussed the Dialogical Self Theory reffering to the multiple selves of people who have to deal with different cultures. Ewing (1990) and Hermans and Kempen (1993) argued that a person could have contrasting or even conflicting identities and still experience her or his life as a whole. Personal life-stories of Iranian refugees were described from multiple cultural points of view: cultural I-positions “I as Iranian”, “I as Dutch” and “I as Iranian/Dutch”. Cultural position themes in self-narratives of thirty Iranian refugees in the Netherlands were considered, and relationships were examined between priorities and values (positive and negative) in the self-narratives. We highlighted positive and negative aspects of the acculturation process, such as homesickness and perceived discrimination. Three important acculturation topics were revealed: relationships (family, spouse, colleagues, and friends), traumatic experiences (flight and prison) and norms and values (Iranian and Dutch). It turned out that many Iranian refugees felt homesick and experienced unfulfilled longings for lost loved ones in Iran. Participating refugees experienced discrimination by mainstreamers, such as colleagues who take advantage of their weak position as immigrants. The present research emphasizes the power of storytelling in relation to acculturation research - the power generated by the experience of wholeness in life of an acculturating person. It was found that it is healthier to acknowledge all “cultural I-positions” and give a place to all experiences of the multiple selves, even conflicting or traumatic ones. By acknowledging the past, one understands the present reactions and ambiguous feelings towards the future. Positive feelings such as enjoyment (e.g., music and sports) can then become a normal way of life once more.